PRICE LISTS FOR AMBER AND THEIR SIGNIFICANCE IN MARKET AND PLANNED REGULATION OF THE ECONOMY - Baranov, P.; Slyvna О.; Korotaiev, V. (Криміналістичний вісник, 2024)
This article examines the role of state price lists in both planned and market economies. State price lists regulate amber economic activity at all levels, including extraction, processing, and sale. In market economies, however, state price lists are meaningless, as the owners of deposits themselves form price lists for each specific object. The current price lists for amber in Ukraine do not include information on the main properties that determine its value, such as colour, transparency, inclusions, and quality of polishing. This lack of information makes it impossible to provide an objective and comprehensive expert evaluation of a particular sample of raw amber. Furthermore, the approved price lists are not linked to specific Ukrainian amber deposits and occurrences. The purpose of this article is to develop an algorithm for creating alternative price lists for raw amber based on real market data and to establish a database. The research methodology is based on general scientific methods such as analytical, dialectical, comparative legal, systemic and structural, comparative and evaluative, as well as special methods such as gemological, economic, integrated development environment, SQL, and C# programming languages. When creating price lists for amber products, it is common to consider the costs of raw materials, manufacturing technology, and sales. The authors propose a methodology for determining the cost of raw materials based on solving an inverse problem. Specifically, the price of raw materials required for a product is calculated based on the price of the product, which already includes the costs of manufacturing technology and sales. This approach introduces scientific novelty to the field. The methodology being considered is based on current data from the real amber market. An alternative method for forming price lists is proposed, which is also based on modern amber market data. The process of creating price lists involves several stages: identifying the product type, determining its consumer properties, establishing the cost of production and manufacturing technology, calculating the yield of usable materials, and determining the cost of raw materials. To ensure objectivity and reliability, the “Amber1” software is used. The data bank, which is created and constantly updated, along with the declarative SQL programming language, offers numerous opportunities for obtaining information on the analysis of the contemporary amber market and its pricing. The results obtained have practical significance for expert studies, research, and education in higher education. They are also relevant to economic, financial, and gemological activities, as well as to the improvement of national legislation in law-making and law enforcement.